2011
DOI: 10.1002/hyp.8194
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evaluation of rainfall estimation by four cumulus parameterization schemes and their sensitivity analysis

Abstract: Abstract:Sustainable water resources management require scientifically sound information on precipitation, as it plays a key role in hydrological responses in a catchment. In recent years, mesoscale weather models in conjunction with hydrological models have gained great attention as they can provide high-resolution downscaled weather variables. Many cumulus parameterization schemes (CPSs) have been developed and incorporated into three-dimensional Pennsylvania State University/National Center for Atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…The reason for the poor goodness of fit with the precipitation datasets may be ascribed to the insufficiency of the parameterization scheme. In this study, the best available cumulus parameterization scheme is used as proposed by several past studies (Ishak et al ., ), indicating that there is a need of further development for a new parameterization scheme especially for the maritime climate. The suitability of data for ETo estimations suggests that ECMWF could be used for hydro‐meteorological applications.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the poor goodness of fit with the precipitation datasets may be ascribed to the insufficiency of the parameterization scheme. In this study, the best available cumulus parameterization scheme is used as proposed by several past studies (Ishak et al ., ), indicating that there is a need of further development for a new parameterization scheme especially for the maritime climate. The suitability of data for ETo estimations suggests that ECMWF could be used for hydro‐meteorological applications.…”
Section: Resultsmentioning
confidence: 99%
“…They can be tuned in terms of domain size, lateral boundary condition (LBC) forcing, horizontal and vertical resolution, and the atmospheric and surface physics (see Cr etat et al 2012). Some model setups have even been found to be seasonally sensitive (Ishak et al 2012). Usually these types of studies focus over a region of interest, or a country or 9496 local area and the models are optimized to get the most accurate results for this location and for a specific season.…”
Section: B Model Biasesmentioning
confidence: 99%
“…Even if certain studies tried to have experimental results reproducible as written by Janjić [8], it is normal that results change when using another model than the experimental one. As introduced in Section 2.3, results clearly show that no convective scheme performs systematically better than the others and that the results are extremely dependent on the internal configuration of the model [52,60]. Despite these individual results, all experiments show that the trends are similar, which suggests that it would be interesting to use all these experiments as part of a model ensemble, as already proposed by Pieri et al [53] and Cortéz-Hernàndez et al [71].…”
Section: Discussionmentioning
confidence: 61%
“…For example, Evans et al [56] and Ratna et al [57] show that BMJ and KFS produce good precipitation patterns respectively in South-East Australia and in South Africa but they both tend to overestimate precipitation amounts while it is the opposite in Madala et al [58] over South East of India. Although Ratna et al [57] show that BMJ is closest to the observed precipitation amount than KFS, Pohl et al [59] show exactly the opposite over the equatorial east Africa and Ishak et al [60] show better performance for KFS during summer and for BMJ during winter over Southwest England. It appears that none of the convective schemes performs systematically better than the others but instead depend on the region, the season or the model configuration, as concluded by Ishak et al [60].…”
Section: Description Of the Convective Schemesmentioning
confidence: 96%
See 1 more Smart Citation